Scale and Scope Economies in Chinese Life Insurance Industry - Lu, Jing (Advances in Social Sciences Research Journal, 2019)
Using the Translog model and the data of all life insurance companies in China from 2012 to 2015, this paper analyzes the scale effect and scope effect in China's life insurance market. In this paper, the premium income of various types of insurance as the output of the company, rent and wages as input elements, Commission and commission expenditure, business and management fees as the operating costs of insurance companies. The results show that both large & medium-sized life insurance companies have economies of scale, and the scale effect of small life insurance companies is significantly stronger than that of large & medium-sized life insurance companies. In terms of scope effect, it is difficult to draw a unified conclusion from the 2012-2015 year's model results. According to the results of the model in 2015, ordinary life insurance and health insurance, health insurance and other insurance have cost-complementary effects.